Computational investigation of thermal behaviors of the automotive radiator operated with water/anti-freezing agent nanofluid based coolant - Ibrahim Ademola Fetuga; Olabode Thomas Olakoyejo; Daniel Ejike Ewim; Joshua Kolawole Gbegudu; Adekunle Omolade Adelaja; Olayinka Omowunmi Adewumi (The Journal of Engineering and Exact Sciences)
In this study, a 3D computational fluid dynamics (CFD) study was conducted in ANSYS (FLUENT) to examine the thermal performance of an automotive radiator using conventional and hybrid coolant with a Al2O3 nanoparticles (NPs) . A hybrid mixture of pure water H2Oand ethylene glycol (EG) in the volumetric proportion of , was coupled with Al2O3 nanoparticles with volume fraction of 1% - 4% at different inlet temperatures. The Reynolds number was varied from 4 000 to 8 000. From the numerical results obtained, it was found that an increase in nanoparticle volume fraction led to an increase in heat transfer rate and pressure drop in the automotive radiator. Also, it was found that at a Reynolds number of 8 000, using the hybrid mixture as a base fluid increased the Nusselt number by 55.6% in contrast to pure water. However, further suspension of 4% Vol. Al2O3 nanoparticles into existing hybrid mixture increased the Nusselt number by 70%. Furthermore, it was found that an increase in the inlet temperature of the radiator caused more enhancement in the heat transfer rate. For Re=8 000 4% vol. Al2O3-water nanofluid, the heat transfer rate was enhanced by 54.57% when increasing the inlet temperature from 60oC to 90oC. Therefore, it is recommended that automobile radiators be operated at a high inlet temperature with nanofluid containing a very high concentration of suitable nanoparticles and an anti-freezing agent in an adequate volumetric proportion to achieve better thermal performance.